Letter from Dr. Carl D. Duncan to Patricia Whiting, October 29, 1964 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Dr. Carl D. Duncan shares characteristics of members of his family for a future event. He discusses a conversation he had with an international student, Amadou Bandé. Also, Duncan attempts to discourage Patricia Whiting from applying to be a Playboy Bunny and encourages her ideas for a term paper.